Численное исследование потокораспределения в укрытии газотурбинной установки, вентилируемом одним и двумя вентиляторами - Кирилаш, Е. И. (НТУ "ХПИ", 2013)
Сформульовано постановку задач про потокорозподіл в укритті ГТУ, що вентилюється одним і двома вентиляторами. Числове розв’язання двох задач з використанням варіанту узагальненої математичної моделі теплового стану укриття дозволило вияснити умови зовнішнього охолодження ГТУ та надати відповідні пропозиції.

Statement of the problem of flux-distribution in gas-turbine enclosure ventilated by one and two fans is defined. Numerical solution of the two problems usingversion of the enclosure heat state generic mathematical model made possible to find out the conditions of gas-turbine external cooling and to give appropriatepropositions.
Numerical investigation of flux-distribution in gas-turbine enclosure ventilated by one and two fans
Keywords: ГТУ; математические модели; вычислительная аэрогидродинамика; вентилятор; охлаждение